58.5k views
0 votes
Help solve both of these questions

Help solve both of these questions-example-1

1 Answer

2 votes
Let's solve for a.
p
x
=
x
3

4
x
2
+
a
Step 1: Flip the equation.
x
3

4
x
2
+
a
=
p
x
Step 2: Add -x^3 to both sides.
x
3

4
x
2
+
a
+

x
3
=
p
x
+

x
3

4
x
2
+
a
=

x
3
+
p
x
Step 3: Add 4x^2 to both sides.

4
x
2
+
a
+
4
x
2
=

x
3
+
p
x
+
4
x
2
a
=

x
3
+
p
x
+
4
x
2

Answer:
a
=

x
3
+
p
x
+
4
x
2
User Anders Kindberg
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.